PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DI SMK NEGERI 1 MAGELANG - Carolus Ryan Putra Praditya; Kir Haryana (Universitas Negeri Yogyakarta, 2020)
This research aims to determine the increase in learning outcomes in the subject of Automotive Basic Technology class X Department of Automotive Engineering SMK Negeri 1 Magelang 2018/2019 Academic Year using the application of cooperative learning models Think Pair Share (TPS) type. This research is a class action research. Data collection techniques used in this study used observation and tests. The steps undertaken in this study were begun with observations to find out the students' initial abilities in the material used, then implemented a Think Pair Share (TPS) type of cooperative learning model with a continuous learning cycle, and ended with a posttest at each end of learning. The results showed that the application of learning using the Cooperative learning model Think Pair Share (TPS) type can improve student learning outcomes in automotive basic technology subjects in class X OC SMK Negeri 1 Magelang. On observation, the average value of 55, in the first cycle the average student learning outcomes of 83, then in the second cycle the average student learning outcomes of 90, thus the average test in the first cycle increased by 28 points or by 56 , 6% compared to observations, the average test in cycle II increased by 7 points or 8.4% compared to the test in cycle I.